Perceptions on the use of personal social networks in the work environment - Bessi, Vânia Gisele; da Rosa Rinker, Caren Maria; Schreiber, Dusan; Bohnenberger, Maria Cristina (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
In this research, authors seek to analyze the perception of managers regarding the use of virtual social networks by members of their teams, as well as the effect of this use on the work activities from the users’ point of view. The article was prepared based on the results of a survey with the students in a higher education institution in Novo Hamburgo/RS. Data were collected by means of a structured questionnaire and were analyzed quantitatively with the use of statistical tests. The results of this study indicate that both managers and users understand that the use of social networking services at work is usual. They believe that excessive accesses can interfere on the team performance. However, both groups have the perception that using social networking services does not have negative effects on the user’s performance, although they understand that leaders need to be aware of some possible signals from their workers.